Prilog istraživanju razvoja bibliografske djelatnosti u Bosni i Hercegovini (1955-2001) / Contribution to the Research on Bibliographic Activity Development in Bosnia and Herzegovina (1955-2001) - Džejla Khattab; Lejla Hajdarpašić; Senada Dizdar (Organizacija Znanja)
In Bosnia and Herzegovina, in 1945, the Decree on Mandatory Delivery of Printed Matters in Bosnia and Herzegovina and the Decree on the National Library of Federal Bosnia and Herzegovina were passed, which laid the legal foundations for creating a Bibliography of Bosniaca. Later in B&H, following the foundation of the B&H Library Association in 1955, the first B&H librarianship journal, the Bulletin of the B&H Library Association and the National Library of the People's Republic of B&H was launched, where the journal was first renamed to Librarianship: Journal of the B&H Library Association and then to Librarianship: Yearbook of the B&H Library Association. In this regard, the goal of this research is to determine the mentioned journal's contribution to Bosnian and Herzegovinian national bibliography and related themes, and to the bibliography as a scientific discipline, in the period from the end of World War II to the beginning of the 21st century. Using the method of content analysis, out of a total of 1,685 papers published in the journal, which were assigned uncontrolled subject headings, 83 published papers dedicated to bibliographic activity in B&H were mapped, which were further classified into thematic blocks based on the available thesaurus for information sciences, with the necessary consideration of the specific B&H context, whereby after a preliminary examination of the corpus, the research was carried out in the period from the beginning of the ninth to the end of the tenth month of 2023. Research results indicate the presence of papers dedicated to the theory of bibliography, current and retrospective bibliography, and related topics of cataloging (before and during the automation of libraries in B&H) and sections / associations / institutions, where the largest number of papers is devoted to cataloging, while the least number of papers is dedicated to the theory of bibliography, in the analysed corpus of journal from 1955 to 2001. In this way, in the time period covered by the research, the journal reflects the foundation and further development of bibliographic activity, and after the war period from 1992-1995, the recovery of bibliographic activity in B&H.